Ghana Poverty Assessment - World Bank (World Bank, Washington, DC, 2020)
After the return to democracy, Ghana achieved significant economic growth and poverty reduction. However, in recent years, the rate of poverty reduction has slowed, becoming insignificant after 2012. The largest reduction in poverty, 2 percent per year, was reached from 1991–1998. Subsequently, the rate of decline fell to 1.4 percent in 1998–2005, 1.1 percent in 2005–2012, and dropped to 0.2 percent per year between 2012 and 2016. The slowdown in poverty reduction was not due to a reduction in GDP per capita growth, which peaked between 2005 and 2012 and remained high between 2012 and 2016. Rather, it was due to a drop in the rate to which economic growth translated into poverty reduction. The growth elasticity of poverty (percentage reduction in poverty associated for every one percentage change in GDP per capita) was 1.2 between 1991 and 1998 but declined to less than 0.1 between 2012 and 2016, indicating a 1 percent increase in GDP per capita led to less than 0.1 percent reduction in poverty.